1996
DOI: 10.1351/pac199668030719
|View full text |Cite
|
Sign up to set email alerts
|

'Naked sugars of the second generation': Asymmetric synthesis of long-chain polypropionates and analogues starting with acetone

Abstract: Homochiral Diels-Alder adduct of 2,4-dimethylfuran to 1-cyanovinyl (1'R)-or (1's)-camphanate are transformed readily into polypropionate fragments containing four or five contiguous stereogenic centres. They can be condensed via cross-aldolizations to lithium enolates of 7-oxabicyclo[2.2.l]heptan-2-ones with high diastereoselectivity generating long--chain systems containing up to eleven stereogenic centres and tertiary alcoholic moieties.A large variety of natural products of biological interest contain polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The alkaline hydrolysis of the latter liberates the chiral auxiliary (a carboxylic acid) which can be recycled. The bicyclic compounds so obtained permitted Vogel and co-workers to prepare several stereotetrads [51,52]. Alternatively, Plumet and Arjona used a Diels-Alder reaction between furan and acrylic acid which provided, after several transformations, a complete library of all possible stereotetrads [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline hydrolysis of the latter liberates the chiral auxiliary (a carboxylic acid) which can be recycled. The bicyclic compounds so obtained permitted Vogel and co-workers to prepare several stereotetrads [51,52]. Alternatively, Plumet and Arjona used a Diels-Alder reaction between furan and acrylic acid which provided, after several transformations, a complete library of all possible stereotetrads [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…They are found in diverse classes of natural products with biological and medicinal interest, [1] and many applied synthetic approaches to polypropionates have been reviewed recently. [2,3] All the synthetic methods are multistep processes involving functional group construction, selective protection steps, and installation of the stereogenic centers. For practical as well as environmental and economic reasons, the number of chemical operations should clearly be reduced to a minimum.…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary communication [8], we showed that the partially protected secoacid of the 9,12-anhydroerythronolide aglycon 6 can be derived from the Diels-Alder adduct (À)-7 of 2,4-dimethylfuran to 1-cyanovinyl (1'S)-camphanate (a −naked sugar of the second generation× [9]) and (3R,4S,5R,6S)-7-benzyloxy-3,5-(isopropylidenedioxy)-4,6-dimethylheptane-2-one (()-8) [10]. We present now the details of these transformations and the conversion of the seco-acid to the corresponding macrolide 9.…”
mentioning
confidence: 99%